Death of a Poet. Epitaphs and Dedications to Vytautas Mačernis - Bernotienė, Gintarė (Colloquia, 2022)
The author of the article examines the corpus of dedications to the poet Vytautas Mačernis, written by poets who lived in Soviet and post-Soviet Lithuania after 1966. The group of epitexts (epitaphs, dedications, and literary letters), scattered in collections of poems and periodicals and united by genre, is analyzed as a series of artefacts confirming the status of Mačernis as a literary classic and revealing the reception of the poet in the community of writers and in the cultural memory of the nation. The formation of Mačernis’s image and the legend about him was influenced by his early death. In turn, it led to a mystification of the poet’s figure and to the attribution to him of almost supernatural powers of a prophet and guardian of the nation. The most significant texts dedicated to Mačernis highlight the gradual stages of poet’s establishment as the youngest poet in the canon of Lithuanian literature and the prevailing, almost fixed trend of romanticizing him and presenting his destiny in an exotic way. The poetic forms of the dedications and the intertextual connections testify to the fact that Mačernis’s works have been recognized as an essential part of the canon.